Peranan Pupuk Magnesium–Sulfur (Kieserit) dalam Memperkuat Efisiensi Pemupukan NPK dan Produktivitas Jagung Manis pada Inceptisol - Mulyani, Oviyanti; Sofyan, Emma Trinurani; Joy, Benny (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
Modern agriculture largely depends on NPK fertilization however, the neglect of secondary nutrients, particularly magnesium (Mg) and sulfur (S), has increasingly led to nutrient imbalances andreduced fertilizer efficiency. Magnesium plays a crucial role in photosynthesis, energy transfer, andenzyme activation, and its deficiency often referred to as the “forgotten element” has become moreprevalent in intensive cropping systems and leached mineral soils. This study aimed to evaluate therole of magnesium–sulfur (Mg–S) fertilizer derived from kieserite in enhancing the growth and yieldof sweet corn (Zea mays saccharata L.) cultivated on Inceptisol soil. This study used a RandomizedBlock Design (RBD) with seven different combination treatments between kieserite (½; ¾; 1; 1 ½ andNPK (¾ and 1) recommended dosages, one treatment recommendation dose of local farmer and onetreatment without fertilizer for comparison. Each treatment was replicated three times, resulting in atotal of twenty-seven experimental plots. Soil chemistry parameters as a main object of thisexperiment. The results of this study showed that the application of kieserite inorganic fertilizersignificantly improved N, P, K, and Mg concentrations in plant tissue, increased total soil Mg content,and enhanced yield components of sweet corn compared to the control and standard NPK treatments.The combined application of one dose of kieserite (300 kg ha⁻¹) and the recommended NPK rate (350–100–50 kg ha⁻¹) produced the highest yield, reaching 14.24 t ha⁻¹, indicating that balanced Mg–Ssupplementation is essential for optimizing nutrient efficiency and maximizing sweet cornproductivity on Inceptisol soils.